Challenges for vaccination in the elderly - Aspinall, Richard; Del Giudice, Giuseppe; Effros, Rita B; Grubeck-Loebenstein, Beatrix; Sambhara, Suryaprakash (Immunity & ageing, 2007)
The increased susceptibility of the elderly to infection presents a major challenge to public health services. An aging immune system is well documented as the cause of increased infection rates in elderly people. Such immunosenescence is multi-factorial and incompletely understood. Immunosenescent changes include malfunctioning of innate immune system cellular receptors; involution of the thymus, with consequent reduction of the naïve T cell population; alteration of the T cell population composition; modified phenotypes of individual T cells; and replicative senescence of memory cells expressing naïve markers. Unfortunately, immunosenescence also renders vaccination less effective in the elderly. It is therefore important that the vaccines used against common but preventable diseases, such as influenza, are specifically enhanced to overcome the reduced immune responsiveness of this vulnerable population.